The intellectual origins of modernity - Oḥanah, Daṿid 1952- (Routledge studies in social and political thought, 2021)
Prologue : the Promethean passion of modernity -- Fom Rousseau to Tocqueville : Janus face of modernity -- 1848 : "We are sitting on a volcano" -- From Marx to Lenin : a red future -- Anarchism, nihilism, racism -- Foucault and beyond -- Epilogue : the end of modernity?